9p+5p+3p-2=

Simple and best practice solution for 9p+5p+3p-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p+5p+3p-2= equation:


Simplifying
9p + 5p + 3p + -2 = 0

Reorder the terms:
-2 + 9p + 5p + 3p = 0

Combine like terms: 9p + 5p = 14p
-2 + 14p + 3p = 0

Combine like terms: 14p + 3p = 17p
-2 + 17p = 0

Solving
-2 + 17p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 17p = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 17p = 0 + 2
17p = 0 + 2

Combine like terms: 0 + 2 = 2
17p = 2

Divide each side by '17'.
p = 0.1176470588

Simplifying
p = 0.1176470588

See similar equations:

| 1-3m=7(m-7) | | 29+9x=101 | | -9/7-9/5w=-9/2 | | 1/2x+7=8 | | 3x+6+2=3(x+2)+2 | | 9=16+-7m | | 17x-7-5x+23=28 | | -0.5*2= | | 1/5n=-7 | | 4a+5-a=-2a | | -3(v-4)=30 | | 11/4x=22 | | 9x-3-2x=-31 | | 3n+7=14+3n | | 4a+6-a=-2a | | 15/9=8/z | | 11/3+3n=4/5n+15 | | 4+x/4=5 | | 3x+17-2x+20=-3 | | 9(3x+6)-6(7x-3)= | | 2x+9+2x+8+2x=2x+2x+3x+8 | | y=0.5x-0.2 | | 40v^2+19v-3=0 | | 4x+7y=-14 | | 4/x=8/40 | | 36-a=-36 | | a/8+7=8 | | 7a=10a/2 | | 10x+89=259 | | 1.33333x+2=0.25x+-9 | | 27=19w | | 2w+w=2(16/3) |

Equations solver categories